Identifikasi Usability User Experience Penggunaan Aplikasi Online Food Delivery dengan Metode USE - Riski Arifin; Rika Sri Utami (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The online food delivery services are currently increasingly being used by the public; this is due to the convenience felt by consumers when using these online services. There are 3 large companies that currently have market share in Indonesia. Competition is not only based on the number of collaborating outlets, apart from the usability of an application. Usability is a measurement of the ease with which an application can achieve its intended use. USE is a usability test based on user experience to see usefulness, ease of use, ease of learning and satisfaction in using the application. This research aims to assess 3 applications from consumer experiences using a use questionnaire. This research used 239 respondents who were divided into 3 application users, namely go-food, grab food, shopee food. The results obtained in this research found that the variables used were very feasible from the value range of 80.99 units to 97.2 units. So it shows that these 3 applications are easy for the public to use and making applications that are easy to use makes online food delivery users net promoters of other users.